The Influence of Perception Price, Perception Quality And Product Design On Repurchase Intention With Perception Value As A Mediation Variable (Case Study Of Brand Mulia Ceramic Consumer In Bandung City) - Arizal Muzahiddan; Fansuri Munawar (Dinasti International Journal of Education Management And Social Science, 2025)
This research aims to examine the influence of price perception, quality perception and product design on repurchase intention with value perception as a mediating variable. The research method used is quantitative with a descriptive verification approach. Researchers use non-probability sampling techniques, namely sampling techniques that do not provide opportunities or opportunities for each member of the population to be selected as a sample. This study selected a sample of 100 people. The tool used to analyze the data in this research is SmartPLS 4. The research results show that (1) price perception has a positive effect on value perception, (2) perception has no positive effect on value perception, (3) product design has a positive effect on value perception, (4) price perception has a positive effect on repurchase interest, (5) quality perception has no positive effect on repurchase interest (6) product design has no positive effect on repurchase interest (7) value perception has a positive effect on repurchase intention, (8 ) price perception has a positive effect on repurchase interest through perceived value, (9) Quality perception does not have a positive effect on repurchase interest through value perception, (10) Product design has a positive effect on repurchase interest through value perception.